Uroporphyrin-accumulating mutant of Escherichia coli K-12. - Săsărman, A (1975)
An uroporphyrin III-accumulating mutant of Escherichia coli K-12 was isolated by neomycin. The mutant, designated SASQ85, was catalase deficient and formed dwarf colonies on usual media. Comparative extraction by cyclohexanone and ethyl acetate showed the superiority of the former for the extraction of the uroporphyrin accumulated by the mutant. Cell-free extracts of SASQ85 were able to convert 5-aminolevulinic acid and porphobilinogen to uroporphyrinogen, but not to copro- or protoporphyrinogen. Under the same conditions cell-free extracts of the parent strain converted 5-aminolevulinic to uroporphyringen, coproporphyrinogen, and protoporphyrinogen. The conversion of porphobilinogen to uroporphyrinogen by cell-free extracts of the mutant was inhibited 98 and 95%, respectively, by p-chloromercuribenzoate and p-chloromercuriphenyl-sulfonate, indicating the presence of uroporphyrinogen synthetase activity in the extracts. Spontaneous transformation of porphobilinogen to uroporphyrin was not detectable under the experimental conditions used [4 h at 37 C in tris(hydroxymethyl)aminomethane-potassium phosphate buffer, pH 8.2]. The results indicate a deficient uroporphyrinogen decarboxylase activity of SASQ85 which is thus the first uroporphyrinogen decarboxylase-deficient mutant isolated in E. coli K-12. Mapping of the corresponding locus by P1-mediated transduction revealed the frequent joint transduction of hemE and thiA markers (frequency of co-transduction, 41 to 44%). The results of the genetic analysis suggest the gene order rif, hemE, thiA, metA; however, they do not totally exclude the gene order rif, thiA, hemE, metA.